L’appropriation locale du discours autochtone : stratégie d’opposition et innovations territoriales dans le conflit foncier de Chocholá (Mexique) - Kelly Redouté (Belgeo)
Since the constitutional reform of 1992, which allows the privatization of ejidal lands, investment projects have multiplied in Mexican ejidos, sometimes giving rise to conflicts. Under the influence of international organizations, ethnicity has become a field of political mobilization of rural populations opposed to these private projects. Based on the study of the Chocholá land conflict in Yucatán, regarding the sale of an ejidal plot for the establishment of a lime factory, this article proposes to examine the process and effects of local ownership of the discourse on the rights of indigenous peoples. It shows that the circulation of indianist discourse involves a reframing of the conflict in terms of collective issues, but that it is also the subject of a territorial translation specific to local concerns. The territorial innovations developed are part of the historical logic of negotiation of the legal framework in the (attempted) production of rules that frame the construction and government of Mexican rural territories. However, they distinguish themselves by seeking to develop “a localized legal order”, that is to say a local rootedness of the law, which makes Chocholá a laboratory in rural governance in the era of indigenous claims.